Effect of additives on diffusion coefficient for cupric ions and kinematics viscosity in cuso4-h2so4 solution at 60°c (2014)
The effect of levelling and grain-refining agents on the diffusion coefficient of cupric ion was studied. Tests were performed using synthetic solutions with Cu2+ concentration and acidity similar to those of a copper electro-refining industrial electrolyte by means of rotating disc electrode (RDE) technique. The diffusion coefficient was calculated according to Levich’s expression from measurements of limiting current for different rotating speed of the RDE. Arrhenius dependence of the diffusion coefficient with temperature in the absence of additives was verified. In presence of additives, the variation of the limiting current is mainly attributed to changes in diffusion coefficient of cupric ion observed.